Monitorowanie procesu pisania w języku obcym. Analiza przerw z perspektywy Teorii Systemów Dynamicznych - Kowal, Iwona (Neofilolog, 2024)
The paper investigates the dynamic character of pausing behaviour in foreign language writing. In a longitudinal study on Polish learners of Swedish, pause length and frequency, as well as the interplay between pause length and the development of lexical diversity, syntactic complexity, accuracy, and fluency, were investigated. According to the assumptions of Dynamic Systems Theory, intra- and inter-subject variability were analysed. The study has shown that the mean length of pauses did not change during the three-year period of second language learning; however, the frequency of pauses significantly decreased, as demonstrated by the increasing number of words written between pauses. There was a considerable variation within subjects during the entire period, and even moderate inter-subject variability was noticed. The occurrence of longer pauses was almost always interconnected with a higher level of accuracy, syntactic complexity, and fluency. This interplay, however, could only be confirmed at the individual level, showing the necessity of following the development of a second language in individuals rather than for the entire group.